Quantifying and Predicting the Influence of Execution Platform on Software Component Performance - Kuperberg, Michael (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2010)
The performance of software components depends on several factors, including the execution platform on which the software components run. To simplify cross-platform performance prediction in relocation and sizing scenarios, a novel approach is introduced in this thesis which separates the application performance profile from the platform performance profile. The approach is evaluated using transparent instrumentation of Java applications and with automated benchmarks for Java Virtual Machines.